CLINICO-NEUROPHYSIOLOGY CHARACTERISTICS OF EPILEPSY IN ELDERLY PATIENTS (Academicia Globe: Inderscience Research, 2022)
Currently, the condition of the patient with epilepsy requires diagnostic control algorithms for dynamic monitoring, as well as methods to enable the patient to calculate the results. The diagnosis of epilepsy is a factor that makes patients nervous and stigmatizing, and has a strong impact. Misunderstanding of the nature of cash flow on the part of patients and the social environment worsened the patient's social life. Deterioration of the quality of life in patients diagnosed with epilepsy should be analyzed using a biopsychosocial concept, which includes the study of clinical, individual-personal and socio-ecological factors.